2021
DOI: 10.20471/acc.2021.60.03.02
|View full text |Cite
|
Sign up to set email alerts
|

Fertility Outcomes after Medical and Surgical Management of Tubal Ectopic Pregnancy

Abstract: and gynecology, division of reproductive endocrinology and infertility, inonu university Faculty of medicine, malatya, turkey SummAry -The objective was to investigate whether the method of treatment (surgical or medical) affects achieving a new pregnancy, as well as the time to and prognosis of the new pregnancy, in women with ectopic pregnancy (eP). information on patients treated in our hospital between 2013 and 2014 for eP was retrieved from the computerized patient records. data on whether these patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 26 publications
2
12
0
Order By: Relevance
“…Available evidence suggests that medical management does not have a negative impact on fertility or future conception probability, not influencing ovarian reserve [42]. Some authors have even found no difference between surgical or medical approach regarding fertility preservation [43]. MTX administration can be systemic or even local under ultrasound guidance, but in a study by Koch et al [27] has been reported that b-hCG clearance is longer when administered locally.…”
Section: Treatment Optionsmentioning
confidence: 99%
“…Available evidence suggests that medical management does not have a negative impact on fertility or future conception probability, not influencing ovarian reserve [42]. Some authors have even found no difference between surgical or medical approach regarding fertility preservation [43]. MTX administration can be systemic or even local under ultrasound guidance, but in a study by Koch et al [27] has been reported that b-hCG clearance is longer when administered locally.…”
Section: Treatment Optionsmentioning
confidence: 99%
“…The literature suggests that there is no difference between the odds of pregnancy formation after medical and surgical treatment for ectopic pregnancy. 22,23 As a limitation of our study, the probabilities of pregnancy formation after treatment were not assessed.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence in literature suggests initial β-hCG levels greater or less than 1500 mIU/mL may provide a method to inform expectant management versus MTX treatment for specific types of EP. 41 , 42 Research has shown that IM MTX injections for patients with confirmed tubal EPs did not result in significantly different outcomes when compared to placebo, especially for clinically stable women with β-hCG < 1500 mIU/mL. 43 Patients with β-hCG > 1500 mIU/mL, however, did have statistically significant changes and negative pregnancy tests after MTX injection compared to placebo.…”
Section: Treatmentmentioning
confidence: 99%
“…Studies such as the DEMETER trial have shown that fertility rates between medical treatment and conservative surgery are not significantly different. 42 , 44 A recent trial exploring the effectiveness of laparoscopic partial tubal resection with end-to-end anastomosis found significantly higher postoperative fallopian tube patency compared to controls. 45 There was no significant difference between ovarian function, operation time, intra blood β-hCG recovery time, and hospital time compared with the control group.…”
Section: Treatmentmentioning
confidence: 99%